Sintesis Biosurfaktan Dari Metil Ester Lemak Ayam : Pengaruh Rasio Mol Metil Ester Lemak Ayam Dengan Trietanolamin Dan Jumlah Katalis KOH - Rahmat Setiawan; Irdoni Irdoni; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The surfactant is a substance which has the ability to reduce surface tension, interface tension, and increase the stability of an emulsion. The Surfactant is an intermediate product which is widely applied in the fields of health, pharmacy, industry, and cleaning products in the household. This study makes biosurfactant from chicken fat. The purpose of this study is to make biosurfactants from chicken fat, to see the effect of mole ratio chicken fat methyl ester with trietanolamine and amount catalyst of KOH on the biosurfactant characterization produced. The preliminary treatment in this study includes preparation of raw materials, extraction of chicken fat by oven method, the degumming process using phosphoric acid at temperature 90°C for 1 hour, gum separation by centrifuge. The transesterification process of methyl ester formation with a mole ratio of oil: methanol 1 : 9, KOH catalyst as much as 2%(b/b) of oil, at temperature 65°C for 6 hours. In the final stage, the transesterification process of chicken fat methyl ester and trietanolamine with operating condition of time is 4 hours and temperature 150°C and agitation speed 200 rpm. The transesterification process with mole ratio variation TEA : chicken fat methyl ester 1 : 2, 1 : 3, 1 : 4 and amount of catalyst variation 3%, 5% and 7%. The best characteristics of biosurfactant were produced at mole ratio 1 : 2, KOH catalyst 3% with the density of 0,922 gr/ml, the pH 9,8, the surface tension of 33,54%, the interface tension of 29,29%, the emulsion stability of 98%, the yield 76,45%, and FT-IR test to ascertain amine functional groups in biosurfactant.Keyword : Biosurfactant, chicken fat, transesterification, triethanolamine